A kind of temperature-sensitive keratin, catalyst, preparation method and application

The temperature-sensitive keratin copper catalyst is prepared by polymerizing functionalized keratin and N-isopropylacrylamide, which solves the problems of low reaction activity and complicated preparation of catalytic materials in the existing technology, and achieves high yield and environmentally friendly β-boron Preparation of acid ester substituted carbonyl compounds.

CN115505079BActive Publication Date: 2025-01-24HUBEI ENG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211223255.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-08
Publication Date
2025-01-24
Estimated Expiration
2042-10-08

AI Technical Summary

Technical Problem

In the prior art, the conversion reaction activity of α,β-unsaturated ketone compounds to be replaced by β-borate carbonyl compounds has low conversion reaction activity, the method of preparing catalytic materials is complex, and there is a lack of a simple, easy-to-operate and high-yield green environmental protection method.

Method used

Through the aggregate keratin and N-isopropyl acrylamide (NIPAAM) polymerization preparation of temperature-sensitive hydrogel PNK, load copper salt to form a temperature-sensitive keratin copper catalyst PNKCU, and the catalyst catalyzed α, β-β-β-at room temperature at room temperature. The unsaturated ketone compound reacts with linked boric acid frequency alcohol, and a pyrinated compounds replaced by β-boric acid are generated.

Benefits of technology

Realize the preparation of cymbal compounds replaced by β-boric acid replacement of high-response activity and high yield. The catalyst has good repetitiveness and recycling, simple production process, environmental protection, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005116388400000011
    Figure FDA0005116388400000011
  • Figure FDA0005116388400000021
    Figure FDA0005116388400000021
  • Figure FDA0005116388400000022
    Figure FDA0005116388400000022
Patent Text Reader

Abstract

The present invention relates to a thermosensitive keratin, a catalyst, a preparation method and an application, and specifically comprises the following steps: (1) functionalizing keratin powder by using 1,2-epoxy-4-vinylcyclohexane, and then reacting the obtained product with N-isopropylacrylamide to obtain a thermosensitive hydrogel, and then loading copper salt to obtain a thermosensitive keratin copper catalyst; (2) characterizing the prepared catalyst; (3) applying the prepared catalyst to the boron addition reaction of chalcone; (4) performing a catalyst recycling test. The thermosensitive keratin copper catalyst PNKCu obtained by the present invention has a low critical temperature, can realize solid-liquid conversion at 25-35°C, has good repeatability and recoverability, and has high reactivity in the boron addition reaction of chalcone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of production of beta-boric acid ester substituted carbonyl compounds, in particular to a temperature-sensitive keratin, a catalyst, a preparation method and an application. Background Art

[0002] Boron addition reaction plays an important role in synthesis. It means that in ether solution, diborane will dissociate into borane, and then react with the unsaturated bonds of alkynes and olefins in the form of BH bonds to generate organic boron compounds. The product generated by this reaction exists as a very important intermediate in synthesis and can be converted into a variety of very important functional groups such as hydroxyl, aryl, alkenyl, etc. through Suzuki coupling reaction. It has important value in the fields of fine chemicals, pharmaceuticals, materials, etc. Recently, the literature (Nanomaterials, 2018 (5)) used divalent copper (1 mol%, relative to the mass percentage of the template reaction substrate) to catalyze the conversion of α, β-unsaturated ketone compounds to β-boronate substituted carbonyl compounds. This work used chalcone as the template substrate, 1.2 equivalents of diboric acid pinacol ester reagent, and a mixed solution of acetone and water as the solvent. Under the condition of room temperature, a high yield of β-boronate substituted carbonyl compounds was obtained. Then, NaBO3·4H2O was used as the oxidant and oxidation was performed at room temperature for 4 hours to obtain hydroxyl substituted carbonyl compounds. However, compared with other copper (II) homogeneous catalytic materials used in this reaction, the reaction activity of this material is relatively low, and compared with other heterogeneous catalytic materials, the preparation method of the catalytic material is more complicated. Therefore, it is very urgent to develop a new green and environmentally friendly method that is simple and easy to operate and can directly convert α, β-unsaturated ketone compounds into β-boronate substituted carbonyl compounds with high yield.

[0003] Due to the excellent properties of keratin itself, keratin is used in many fields. For example, in the food industry, keratin can be made into food additives because it contains a lot of umami amino acids. In the biomedical field, keratin alone or in combination with other biomaterials can be used to make materials such as bone regeneration, wound healing, hemostasis, and peripheral nerve repair. In the cosmetics industry, its high resistance and special biological effects can be used as raw materials to make some daily cosmetics, such as sunscreen and shampoo. In tissue engineering, due to its excellent biocompatibility and activity, it is expected to become a substitute for tissue engineering. In addition, keratin also plays an important role in fertilizers, pesticides, and environmental protection.

[0004] Near the critical temperature (LCST), PNIPAAm hydrogel has volume phase transition properties of hydrophobic / hydrophilic and chain curling / stretching. Due to these characteristics, the catalyst formed by PNIPAAm hydrogel composite metal ions is easy to recover near the LCST. When the temperature of the reaction system is lower than the LCST, the catalyst will be dissolved in the aqueous solution to form a transparent solution. When the temperature of the reaction system is higher than the LCST, the catalyst will precipitate, which realizes the effective reuse and convenient recovery of the catalyst, making this type of catalyst more economical, green and environmentally friendly. At present, there is no report on the application of temperature-sensitive keratin-loaded copper catalyst in the boron addition reaction of constructing CB bonds. Summary of the invention

[0005] In order to prepare a green catalyst with high reaction activity and easy recovery, the present invention uses functionalized keratin and N-isopropylacrylamide (NIPAAm) to react to prepare a thermosensitive hydrogel PNK, and the dried hydrogel is loaded with copper salt to prepare a thermosensitive keratin copper catalyst PNKCu.

[0006] The technical concept of the present invention is to prepare a thermoresponsive hydrogel by polymerizing the thermosensitive material N-isopropylacrylamide and functionalized keratin, and to make it catalytically active by loading divalent copper salt. During the catalytic reaction, it can be homogeneously dissolved in the solvent, and after the reaction is completed, the catalyst can be separated by changing its overall temperature.

[0007] A thermosensitive keratin having the following structural formula,

[0008]

[0009] Among them, R represents the serine, threonine, tyrosine, lysine, and arginine residues in the keratin molecule, and a+b=12-13.

[0010] Furthermore, m:n=50-90:10, 90 represents the degree of polymerization of N-isopropylacrylamide, and 10 represents the degree of polymerization of keratin.

[0011] Furthermore, a:b≤3:10.

[0012] A method for preparing temperature-sensitive keratin, comprising the following preparation method:

[0013] Step 1.1: functionalization of keratin: dissolving keratin powder and 1,2-epoxy-4-vinylcyclohexane in ionized water, stirring to obtain a mixed solution, then adding the mixed solution dropwise into acetone, filtering to obtain a precipitate, then repeatedly washing the precipitate with acetone, and finally vacuum drying at 50-70°C to obtain functionalized keratin;

[0014] Step 1.2: Polymerization with thermosensitive material: The product obtained in step 1.1 and the thermosensitive material N-isopropylacrylamide (NIPAAm) are dissolved in deionized water and polymerized to obtain a thermosensitive hydrogel solution, and then an initiator is added to carry out a copolymerization reaction. The product of the copolymerization reaction is then placed in a dialysis bag and dialyzed with deionized water, and finally dried in an oven to obtain a thermosensitive keratin gel.

[0015] Furthermore, in step 1.2, the initiator is ammonium persulfate, the initiation temperature is 60° C., and the polymerization time is 24 h.

[0016] Furthermore, in the acetone solution in step 1.1, the mass ratio of acetone to solution is 10:1, the stirring temperature in step 1.1 is 60° C., and the stirring time is 24 h.

[0017] A catalyst containing thermosensitive keratin is prepared by dissolving a water-soluble divalent copper salt in deionized water, mixing the mixture with the thermosensitive keratin gel, stirring the mixture at room temperature for 24 hours, and freeze-drying the mixture to obtain a thermosensitive keratin copper catalyst.

[0018] Furthermore, the water-soluble divalent copper salt is one or more of copper sulfate, copper nitrate, and copper chloride.

[0019] Furthermore, the Cu in the catalyst 2+ The molar ratio of keratin to thermosensitive keratin is 1:10.

[0020] Application of a catalyst containing thermosensitive keratin in the synthesis of β-boric acid ester substituted carbonyl compounds, using α, β-unsaturated ketone compounds and biboric acid pinacol ester as raw materials, using a catalyst containing thermosensitive keratin as a catalyst, stirring evenly at room temperature to prepare β-boric acid ester substituted carbonyl compounds;

[0021] The structural formula of the α,β-unsaturated ketone compound is The corresponding β-boronic acid ester substituted carbonyl compound has the following structural formula:

[0022] Among them, R1 is one of phenyl, p-methylphenyl, and p-methoxyphenyl, and R2 is one of phenyl, p-methylphenyl, p-methoxyphenyl, p-fluorophenyl, p-chlorophenyl, p-bromophenyl, o-chlorophenyl, m-bromophenyl, and m-chlorophenyl.

[0023] Further, the preparation method of the β-boronic acid ester substituted carbonyl compound comprises the following steps:

[0024] Step P1, take α, β-unsaturated ketone compound, bipyraclostrobin, and catalyst containing thermosensitive keratin in a molar ratio of 1:1.2:0.01, add them to the solvent, and stir at room temperature for 6-24h; the molar ratio of thermosensitive keratin copper catalyst is 1:1.2:0.01. 2+ as a benchmark;

[0025] Step P2, extracting the product obtained in step P1 with an organic solvent, drying, rotary evaporating, and finally separating by column chromatography to obtain a β-boronic acid ester substituted carbonyl compound;

[0026] In the step P2, the volume ratio of ethyl acetate to petroleum ether used for column chromatography is 1:4, the solvent is methanol, and the organic solvent is ethyl acetate.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The thermosensitive keratin prepared by the present invention is used as the basis for preparing a catalyst loaded with a large amount of metallic copper, and finally obtaining a thermosensitive keratin copper catalyst. Since a C=C-containing group can be grafted onto the keratin after the keratin reacts with 1,2-epoxy-4-vinylcyclohexane, the functionalized keratin can be better grafted and copolymerized with the hydrophilic monomer N-isopropylacrylamide (NIPAAm). The copolymer product thus formed has a rich pore structure with a diameter of 5 to 10 μm, a large size, and is stacked together, so that a large amount of metallic copper can be loaded, thereby making the catalyst have a stronger catalytic activity.

[0029] 2. The present invention also provides an application based on a thermosensitive keratin copper catalyst, using α,β-unsaturated ketone compounds and biboric acid pinacol ester as raw materials, and using a thermosensitive keratin copper catalyst to prepare β-boric acid ester substituted carbonyl compounds. The reaction conditions of the entire preparation process are mild, no need to add any base, methanol is used as a solvent, and the reaction is carried out at room temperature, which is simple and easy to operate. Due to the high activity of the catalyst, the β-boric acid ester substituted carbonyl compound prepared based on the catalyst has a high product yield of more than 80%, and the yield of some specific β-boric acid ester substituted carbonyl compounds is as high as 92%. In addition, the catalyst can catalyze various types of α,β-unsaturated ketone compounds to complete the boron addition reaction, and the substrate has a wide range of applications.

[0030] 3. The keratin in the catalyst proposed by the present invention has the characteristic of low critical temperature after graft copolymerization with the thermosensitive material. When the catalyst is recovered, the solid-liquid conversion can be achieved by adjusting the temperature to 25-35°C, that is, the product and the catalyst can be separated into solid and liquid through a simple temperature change. It has good repeatability and recyclability, and the recovered catalyst still has high catalytic activity and a long cycle life. Therefore, the production and preparation costs of the catalyst and the subsequent use process are very low, which is environmentally friendly and avoids environmental pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM morphology of the temperature-sensitive material PN90K10Cu;

[0032] Figure 2 XRD patterns of thermosensitive materials keratin powder, functionalized keratin, PN90K10, and PN90K10Cu;

[0033] Figure 3 This is the LCST test spectrum of the temperature-sensitive material PN90K10Cu;

[0034] Figure 4 is the H NMR spectrum of the target product in Application Example 1;

[0035] Figure 5 is the NMR carbon spectrum of the target product in Application Example 1;

[0036] Figure 6 This is a study chart on the repeatability and recovery performance of the temperature-sensitive material PN90K10Cu. DETAILED DESCRIPTION

[0037] The technical scheme of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative labor conditions belong to the scope of protection of the present invention. In order to better understand the present invention, the present invention will be described in detail below in conjunction with the accompanying drawings and specific examples. Specifically, it is manifested in the preparation and application of the temperature-sensitive keratin copper catalyst, the catalytic performance test of the temperature-sensitive keratin copper catalyst material, and the recyclable performance test.

[0038] Example 1

[0039] The temperature-sensitive keratin copper catalyst provided in this embodiment has a functionalized keratin powder as a carrier, N-isopropylacrylamide as a hydrophilic monomer, and ammonium persulfate (APS) as an initiator, which is prepared in deionized water and then adsorbs copper ions to form a temperature-sensitive keratin copper catalyst. The specific preparation method is:

[0040] S1. Weigh 1.9987g of dry hydrolyzed keratin powder, measure 20mL of deionized water and pour into a 100mL round-bottom flask, put in a stirrer of appropriate size, plug the flask mouth with a rubber stopper, stir at 60℃ for 24h to dissolve it (10wt% solution); then add 0.3618g of 1,2-epoxy-4-vinylcyclohexane, react at 50-70℃ for 24h under magnetic stirring, then transfer the reaction medium dropwise into acetone under strong stirring (acetone: solution mass ratio = 10:1) to precipitate functionalized keratin. Collect the precipitate and wash it with acetone several times, then vacuum dry it at 60℃ for 24h to obtain functionalized keratin; in this step, the molar ratio of keratin to 1,2-epoxy-4-vinylcyclohexane is 10:3.

[0041] S2, weighing 1.7985g N-isopropylacrylamide (NIPAAm) and 0.2019g of the functionalized keratin prepared in step S1 into a round-bottom flask, dissolving them in 20mL of deionized water to obtain a 10wt% NIPAAm solution containing keratin; at 60°C, using 0.1039g of ammonium persulfate (APS) as an initiator, free radical polymerization is carried out with the NIPAAm solution containing keratin, and the reaction time is 24h. The amount of ammonium persulfate added is 5% of the total amount of N-isopropylacrylamide. Less amount will result in incomplete polymerization, and excessive amount will result in a smaller molecular weight of the polymer and failure to form a pore structure.

[0042] After the reaction was completed, the reaction product was poured into a dialysis bag and dialyzed with deionized water for 24 hours, and then placed in an oven for drying for 4 hours to obtain a thermosensitive keratin hydrogel; in this step, the molar ratio of N-isopropylacrylamide to keratin was 90:10.

[0043] S3, weigh 0.499g CuSO4 crystals with an electronic balance, dissolve it in 50mL deionized water to prepare a CuSO4 aqueous solution, measure 25mL of the prepared CuSO4 solution, pour it into a beaker, and weigh 0.1002g of the dried thermosensitive keratin hydrogel prepared in step S2 and pour it into a beaker, so that it adsorbs metallic copper ions, stir at room temperature for 24h, and then freeze-dry first. After 24h, a freeze-dried thermosensitive keratin copper catalyst is obtained. In this step, Cu 2+ The molar ratio of keratin to thermosensitive keratin is 1:10.

[0044] In this embodiment, 1,2-epoxy-4-vinylcyclohexane can also be replaced by other organic substances A having C=C double bonds and epoxy groups. The C=C double bonds can be polymerized with N-isopropylacrylamide, and the epoxy groups can be connected to the carboxyl groups of amino acids after ring opening.

[0045] For example, the structural formula of organic compound A is: X is =CH- or =N-, Y is -NH-, -NR 4 -, -S-, -O-, -CH=N-, -N=CH-, -N=N-, -CH=CH-, R 1 is H, or an optionally substituted lower alkyl group, R 5 , R 6 or R 7 It is an optionally substituted lower aryl group, an optionally substituted lower heterocyclic ring containing a nitrogen atom, an optionally substituted lower alkoxy group, or an optionally substituted amino group.

[0046] The keratin and 1,2-epoxy-4-vinylcyclohexane provided in this embodiment are purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd., N-isopropylacrylamide (NIPAAm) is purchased from Shanghai McLean Pharmaceutical Technology Co., Ltd., and copper sulfate is purchased from Tianjin Kaitong Chemical Reagent Co., Ltd. The carboxylic acid group in keratin has good reactivity and can be easily modified and grafted. Keratin can immobilize metal ions through coordination and electrostatic effects. However, keratin itself does not have temperature-sensitive properties, so temperature-sensitive properties can be obtained by polymerization with N-isopropylacrylamide (NIPAAm), and solid-liquid separation can be achieved by changing the temperature. The water-soluble divalent copper salt is one of copper sulfate, copper nitrate, and copper chloride.

[0047] like Figure 1 This is a SEM scanning electron microscope image of the thermosensitive material PN90K10Cu prepared in Example 1. Attached figure b in the figure is a partial view of attached figure a, from which it can be seen that the keratin obtained has a pore structure with a diameter of 5 to 10 μm, which is relatively large in size and is stacked together with some agglomeration.

[0048] Figure 2 This is the XRD spectrum of the thermosensitive material PN90K10Cu prepared in Example 1. According to the XRD curve analysis, the keratin powder (a) has a relatively large and blunt crystal peak at 12.4°, which is the overlapping peak of the α-helix structure and the β-folding structure; 18.9° and 26° have relatively blunt peaks with very small diffraction intensities, which are the α-helix characteristic peak and the α-folding characteristic peak, respectively. From the XRD curve of keratin, it can be analyzed that the main arrangement of keratin is α-helix structure, β-helix structure and amorphous arrangement. Compared with keratin powder (a), functionalized keratin (b) has a diffraction peak at the same position, but it is relatively low and wide.

[0049]

[0050] This is because the reaction between keratin and 1,2-epoxy-4-vinylcyclohexane reduces the intermolecular force, increases the intermolecular distance, and slightly disturbs the order of the molecular chain, which weakens the crystallization performance. The reaction between keratin and 1,2-epoxy-4-vinylcyclohexane is as follows:

[0051]

[0052] 1,2-epoxy-4-vinylcyclohexane can be grafted onto keratin. On the one hand, the carboxyl and amino ring structures inside keratin are disrupted, and the original smaller ring structure is changed, thereby forming the structure of the grafted product in the above formula. The functionalized keratin can then form a larger ring structure with the help of the hydroxyl group of 1,2-epoxy-4-vinylcyclohexane. On the other hand, the functionalized keratin is rich in double bonds, so it can be better grafted and copolymerized with N-isopropylacrylamide (NIPAAm), which is a thermosensitive material and also a hydrophilic monomer, making the overall stability of the catalyst stronger. The structure of the thermosensitive keratin gel is shown in Formula 2, where a:b=3:10, m:n=90:10, a+b=12~13, and the molar ratio of keratin to 1,2-epoxy-4-vinylcyclohexane and N-isopropylacrylamide is 10:3:90. When the functionalized keratin forms a ring structure inside itself, the cavity size is appropriate. One is to load an appropriate amount of Cu 2+ The second is to leave room for the catalytic reaction, making the catalytic efficiency higher. If the amount of 1,2-epoxy-4-vinylcyclohexane is increased, the ring structure formed by the functionalized keratin will become larger or disappear.

[0053]

[0054] like Figure 2 As shown in the figure, the peak positions of PN90K10 (c) and functionalized keratin (b) are basically the same and slightly wider, but the peak at 26° disappears, indicating that the chemical bonds between the functionalized keratin (b) and the keratin structure are destroyed after the polymerization of NIPAAm, so more amorphous regions are generated during the formation of PN90K10. Compared with PN90K10 (b), PN90K10Cu (d) has many sharp and medium-intensity peaks at multiple angles such as 18°, 22°, and 24°, indicating that copper loading in the hydrogel enhances its crystallization performance. It is also possible that the copper ions are not fully loaded, and the remaining copper sulfate crystals after freeze-drying make the XRD curve show a high degree of crystallinity.

[0055] Figure 3This is the LCST test spectrum of the thermosensitive material PN90K10 in Example 1. Its critical solution temperature is 30°C. It exhibits good solubility below the LCST and forms a uniform and transparent aqueous solution. Above the LCST, the hydrogel exhibits hydrophobicity and precipitates from the aqueous phase. This property enables the effective reuse and convenient recovery of the catalyst prepared with the thermosensitive hydrogel as a carrier.

[0056] Application Example 1

[0057] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 to prepare a β-boric acid ester-substituted carbonyl compound. The specific steps are as follows:

[0058] P1, take chalcone (0.2mmol), biboric acid pinacol ester (0.24mmol), thermosensitive keratin copper catalyst 0.002mmol (Cu 2+ The mixture was added to 2 mL of methanol solvent and stirred at room temperature for 12 h to obtain the boron addition product. The Cu in the thermosensitive keratin copper catalyst 2+ The content is 1% of the molar fraction of the reaction raw material chalcone;

[0059] P2, extract with ethyl acetate, dry, rotary evaporate, and finally separate by column chromatography to obtain the carbonyl compound substituted with β-boronic acid ester. The product yield is 92%. The reaction process is:

[0060]

[0061] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below. Figure 4 and Figure 5 .

[0062] 1 H NMR (400MHz, Chloroform-d); δ=8.01–7.98(m,2H),7.59–7.56(m,1H),7.55–7.48(m,2H),7.46–7.44( m,4H),7.25–7.14(m,1H),3.62–3.40(m,2H),2.80(dd,J=11.0,5.0Hz,1H),1.27(s,6H),1.19(s,6H).

[0063] 13 C NMR (100MHz, Chloroform-d); δ=199.5,141.7,136.5,132.7,128.3,128.2,128.1,127.8,125.4,83.1,43.1,24.38,24.33.

[0064] Application Example 2

[0065] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts a method basically the same as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-3-(4-p-chlorophenyl)-1-2-ene-1-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 92%. The reaction process is:

[0066]

[0067] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below: 1 H NMR (400MHz, Chloroform-d); δ=7.99–7.96(m,2H),7.59–7.54(m,1H),7.49–7.42(m,2H),7. 27–7.25(m,4H),3.57–3.35(m,2H),2.81(dd,J=10.3,5.3Hz,1H),1.26(s,6H),1.19(s,6H).

[0068] 13 C NMR (100MHz, Chloroform-d); δ=199.5,140.1,136.5,133.1,131.2,129.6,128.6,128.5,128.2,83.4,43.1,24.6,24.5.

[0069] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-3-(4-p-chlorophenyl)-1-2-ene-1-one is also very high, and the yield of its boron addition reaction product reaches 92%.

[0070] Application Example 3

[0071] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts the same method as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-3-(4-p-bromophenyl)-1-2-ene-1-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 83%. The reaction process is:

[0072]

[0073] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below: 1H NMR (400MHz, Chloroform-d); δ=7.90–7.86(m,2H),7.50–7.44(m,1H),7.39-7.31(m,2H),7.34–7.31( m,2H),7.12–7.08(m,2H),3.47–3.31(m,2H),2.69(dd,J=10.3,5.4Hz,1H),1.17(s,6H),1.09(s,6H).

[0074] 13 C NMR (100MHz, Chloroform-d); δ=199.5,141.2,136.7,133.2,131.6,130.3,128.7,128.2,119.5,83.6,42.9,24.7,24.6.

[0075] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-3-(4-p-bromophenyl)-1-2-ene-1-one is also very high, and the yield of its boron addition reaction product reaches 83%.

[0076] Application Example 4

[0077] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts a method basically the same as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-3-(4-p-methoxyphenyl)-1-2-ene-1-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 86%. The reaction process is:

[0078]

[0079] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below: 1 H NMR (400MHz, Chloroform-d); δ = 7.97 (d, J = 8.8Hz, 2H), 7.38–7.28 (m, 4H), 7.18 (t, J = 6.9Hz, 1H), 6.95 (d ,J=8.9Hz,2H),3.89(s,3H),3.57–3.39(m,2H),2.80(dd,J=10.8,5.2Hz,1H),1.27(s,6H),1.19(s,6H).

[0080] 13C NMR (100MHz, Chloroform-d); δ=198.1,163.2,142.0,130.2,129.8,128.4,128.3,125.4,113.5,83.2,55.4,43.0,24.58,24.55.

[0081] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-3-(4-p-methoxyphenyl)-1-2-ene-1-one is also very high, and the yield of its boron addition reaction product reaches 86%.

[0082] Application Example 5

[0083] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts the same method as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-1-(4-m-methylphenyl)-1-2-ene-3-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 80%. The reaction process is:

[0084]

[0085] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below: 1 H NMR (400MHz, Chloroform-d); δ=7.92–7.87(m,2H),7.48–7.44(m,1H),7.39–7.34(m,2H),7.13–7.01(m,3H),6 .93(d,J=7.4Hz,1H),3.51–3.31(m,2H),2.68(dd,J=11.0,4.9Hz,1H),2.25(s,3H),1.18(s,6H),1.10(s,6H).

[0086] 13 C NMR (100MHz, Chloroform-d); δ=199.7,141.7,138.0,136.7,132.8,129.2,128.4,128.3,128.0,126.3,125.2,83.3,43.3,24.5,21.4.

[0087] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-1-(4-m-methylphenyl)-1-2-ene-3-one is also very high, and the yield of its boron addition reaction product reaches 80%.

[0088] Application Example 6

[0089] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts the same method as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-1-(4-p-methoxyphenyl)-1-2-ene-3-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 84%. The reaction process is:

[0090]

[0091] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below: 1 H NMR (400MHz, Chloroform-d); δ=7.99–7.96(m,2H),7.35–7.27(m,4H),7.21–7.16(m,1H),6.94–6. 91(m,2H),3.88(s,3H),3.58–3.38(m,2H),2.80(dd,J=10.8,5.2Hz,1H),1.27(s,6H),1.19(s,6H).

[0092] 13 C NMR (100MHz, Chloroform-d); δ=198.3,163.3,142.2,130.2,129.8,128.4,128.3,125.4,113.5 83.2,55.5,43.0,24.58,24.55.

[0093] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-1-(4-p-methoxyphenyl)-1-2-ene-3-one is also very high, and the yield of its boron addition reaction product reaches 84%.

[0094] Application Example 7

[0095] This application example uses the temperature-sensitive keratin copper catalyst of Example 1 above, and adopts the same method as that of Application Example 1 to prepare a β-boric acid ester substituted carbonyl compound. The only difference is that the α,β-unsaturated ketone compound selected in this application example is (E)-1-(4-p-methylphenyl)-1-2-ene-3-one. Finally, a β-boric acid ester substituted carbonyl compound is obtained, and the product yield is 85%. The reaction process is:

[0096]

[0097] The NMR hydrogen spectrum and carbon spectrum of the target product are shown below

[0098] 1 H NMR (400MHz, Chloroform-d); δ=7.78–7.77(m,2H),7.24–7.16(m,4H),7.15(d,J=8.0Hz,2H),7.11–7 .06(m,1H),3.48–3.27(m,2H),2.70(dd,J=10.9,5.0Hz,1H),2.30(s,3H),1.16(s,6H),1.08(s,6H).

[0099] 13 C NMR (100MHz, Chloroform-d); δ=199.4,143.8,142.2,134.2,129.1,128.4,128.3,128.3,125.5,83.3,43.1,24.60,24.57,21.7.

[0100] This application example shows that under the catalytic conditions of the temperature-sensitive keratin copper catalyst provided in the embodiment of the present invention, the conversion rate of (E)-1-(4-p-methylphenyl)-1-2-ene-3-one is also very high, and the yield of its boron addition product reaches 85%.

[0101] It can be seen from the above application examples 1-7 that α, β-unsaturated ketone compounds can be used to prepare corresponding β-boric acid ester-substituted carbonyl compounds using the temperature-sensitive keratin copper catalyst provided by the present invention using various α, β-unsaturated ketone compounds with high yield.

[0102] Application Example 8

[0103] The temperature of Application Example 1 was repeatedly raised and lowered to test the recyclability of the catalyst. Figure 6 As shown in a, the results show that the transmittance does not change significantly after multiple heating and cooling, indicating that the catalyst has good recyclability. Figure 6 b shows that the catalyst was used repeatedly 5 times to catalyze the boron addition reaction with chalcone as substrate, and the yield of the boron addition reaction did not decrease significantly.

[0104] Application Example 8 shows that the catalyst has good recoverability and effective repeatability.

Claims

1. A thermosensitive keratin, characterized in that: Has the following structural formula, Wherein, R represents serine, threonine, tyrosine, lysine, and arginine residues in the keratin molecule, a+b=12-13, a:b≤3:10; m:n=50-90:10, 50-90 represents the degree of polymerization of N-isopropylacrylamide, and 10 represents the degree of polymerization of keratin.

2. A method for preparing a thermosensitive keratin, characterized in that The invention comprises the following preparation method, Step 1.1 functionalization of keratin: dissolving keratin powder and 1,2-epoxy-4-vinylcyclohexane in ionized water, stirring to obtain a mixed solution, then adding the mixed solution dropwise into acetone, filtering to obtain a precipitate, then repeatedly washing the precipitate with acetone, and finally vacuum drying at 50-70° C. to obtain functionalized keratin, wherein the molar ratio of keratin to 1,2-epoxy-4-vinylcyclohexane is 10:3; Step 1.2: Polymerization with thermosensitive material: The product obtained in step 1.1 and the thermosensitive material N-isopropylacrylamide (NIPAAm) are dissolved in deionized water and polymerized to obtain a thermosensitive hydrogel solution, and then an initiator is added to carry out copolymerization reaction. The product of the copolymerization reaction is then placed in a dialysis bag and dialyzed with deionized water, and finally dried in an oven to obtain a thermosensitive keratin gel, wherein the molar ratio of N-isopropylacrylamide to keratin is 90:

10.

3. The method for preparing the thermosensitive keratin according to claim 2, characterized in that: In the step 1.2, the initiator is ammonium persulfate, the initiation temperature is 60° C., and the polymerization time is 24 h.

4. The method for preparing the thermosensitive keratin according to claim 2, characterized in that: In the acetone solution obtained by mixing acetone with the mixed liquid in the step 1.1, the mass ratio of acetone to the mixed liquid is 10:

1. In the step 1.1, the stirring temperature is 60° C. and the stirring time is 24 hours.

5. A catalyst containing the temperature-sensitive keratin prepared as claimed in claim 2, characterized in that: The water-soluble divalent copper salt is dissolved in deionized water, and then mixed with the temperature-sensitive keratin gel, stirred at room temperature for 24 hours, and then freeze-dried to obtain the temperature-sensitive keratin copper catalyst.

6. The catalyst according to claim 5, characterized in that The water-soluble divalent copper salt is one or more of copper sulfate, copper nitrate and copper chloride.

7. The catalyst according to claim 5, characterized in that The Cu in the catalyst 2+ The molar ratio of keratin to thermosensitive keratin is 1:

10.

8. Use of a catalyst containing thermosensitive keratin as claimed in any one of claims 5 to 7 in the synthesis of β-boric acid ester substituted carbonyl compounds, characterized in that: Using α,β-unsaturated ketone compounds and biboric acid pinacol ester as raw materials and a catalyst containing thermosensitive keratin as a catalyst, stirring evenly at room temperature to prepare a β-boric acid ester substituted carbonyl compound; The structural formula of the α,β-unsaturated ketone compound is The corresponding β-boronic acid ester substituted carbonyl compound has the following structural formula: Among them, R1 is one of phenyl, p-methylphenyl, and p-methoxyphenyl, and R2 is one of phenyl, p-methylphenyl, p-methoxyphenyl, p-fluorophenyl, p-chlorophenyl, p-bromophenyl, o-chlorophenyl, m-bromophenyl, and m-chlorophenyl.

9. The use according to claim 8, characterized in that: The method for preparing a β-boronic acid ester substituted carbonyl compound comprises the following steps: Step P1, take α, β-unsaturated ketone compound, bipyraclostrobin, and catalyst containing thermosensitive keratin in a molar ratio of 1:1.2:0.01, add them to the solvent, and stir at room temperature for 6-24h; the molar ratio of thermosensitive keratin copper catalyst is 1:1.2:0.

01. 2+ as a benchmark; Step P2, extracting the product obtained in step P1 with an organic solvent, drying, rotary evaporating, and finally separating by column chromatography to obtain a β-boronic acid ester substituted carbonyl compound; In the step P1, the solvent is methanol; in the step P2, the volume ratio of ethyl acetate and petroleum ether used for column chromatography is 1:4, and the organic solvent is ethyl acetate.

Citation Information

Patent Citations

  • Preparation of eggshell membrane supported catalyst and application of catalyst in synthesis of dihydropyrimidine compounds

    CN105903493A

  • Methods for controlling peptide solubility, chemically modified peptides, and stable solvent systems for producing same

    WO2003035722A1